The Islamic Malay traditional towns, learning through the attributes special emphasis on Johor Bahru, Malaysia - Remaz Ossen, Dilshan; Idid, Syed Zainol Abidin; Abdul Aziz, Zul Azri (2010)
the effect of culture and religion on spatial configuration of organic cities is well noticeable in formation of the islamic Malay Traditional Towns, In the process of formation and evolution of those towns, thoughts, beliefs and emotions of the public were manifested. Accordingly, the aforementioned towns were located in the river mouth or 'Kuala' and the town shape expanded from the town center. In its most basic form, the traditional towns consisted of six components, which are; the river, the palace, the mosque, the open field, the commercial centre and the indigenous settlements. Out of these six, the three basic elements; the Palace. Mosque and Field or 'Padang' formed the planning base of the Malay towns thaht displayed the relationship between the religion, the ruler and the people. Rapid urbanization and development has brought about irreplaceable changes to the Islamic Malay traditional Towns. Although some features of the traditional town can still be traced, it is feared that by the end of this area, there will be any evidences of such significant identity. The discussion of Islamic malay Traditional Towns are hampered by three interconnected factors-inadequacy of research interest and input, rehabilitation and conservation of old city areas and monuments received little attention in urban development policy, lack of understanding of formation of these towns with respect to tradition, religion and beliefs of the people. The principle objective of this paper is to present empirical overview of the significant attributes and formation of Malay Traditional Towns. The paper finally presents an urban model of morphology and spatial organization with considerations on the need for area rehabilitation of Malay traditional town. Their sustainability and revitalisation will be most feasible if they are integrated into new concepts of the present day requirements.